Pendampingan Kelompok Sadar Wisata Pantai Tlangoh Menuju “Blue Marine Economy” Berbasis Pariwisata Halal - Muhammad Anas; Fauzie Senoaji; Gusmaniarti Gusmaniarti (Indonesian Journal Publisher, 2025)
The background of the community service (PKM) with the following problems; Firstly, towards the